ANALYSIS OF THE BASIC DEFINITIONS OF THE RESEARCH ON THE DEVELOPMENT OF TEACHERS' RESEARCH COMPETENCE OF THE UKRAINIAN LANGUAGE AND LITERATURE - Serdiuk, Halyna (Professional Pedagogics, 2023)
The relevance of the development of the research orientation of pedagogical activity is determined by the modern paradigm of education, which requires a teacher capable of organizing research-oriented education; relevance is also due to the objective need to formulate comprehensive definitions of the basic concepts of the investigated problem of the development of the research competence of a Ukrainian language and literature teacher in the system of scientific and methodological work of the lyceum.The purpose of the article is to analyze modern studies regarding the issue of the research competence development of the Ukrainian language and literature teacher, to carry out a terminological analysis of the conceptual and categorical apparatus of the scientific problem, to clarify the logical and semantic content of the basic concepts of the study: "Ukrainian language and literature teacher ", "research competence of a Ukrainian language and literature teacher".Methods: study of scientific sources, psychological-pedagogical and scientific-methodological literature, legislative acts and normative-legal documents – to find out the degree of the problem development; generalization and systematization – to generalize the theoretical foundations of the researched problem, clarify the content of the concepts: "Ukrainian language and literature teacher ", "research competence of the teacher"; definitive analysis – to clarify the logical-semantic content of the basic research concepts " Ukrainian language and literature teacher", "research competence of the Ukrainian language and literature teacher ".Results: the analysis and systematization of modern scientific research on the problem of the development of the research competence of a philology teacher was carried out, the basic concepts of the scientific problem of the development of the research competence of the teacher of the Ukrainian language and literature were identified and characterized, and the generic-species relations between the basic and related concepts were established.Conclusions: the meaning of the concept of "Ukrainian language and literature teacher" has been clarified (a specialist in the linguistic and literary field of knowledge, who has fundamental theoretical training in professional disciplines, has modern teaching methods and learning technologies, provides quality teaching of the Ukrainian language and literature, solves educational, innovative, methodological, research problems and creates a socio-cultural environment in an educational institution); the content of the definition " research competence of the Ukrainian language and literature teacher" has been clarified (an integrative and professional property of a person, which synthesizes personal and reflective qualities, favorable for the realization of a philologist teacher in research activities; contains a system of values and motivation to carry out scientific research in the field of philology, methodology, pedagogy; knowledge, abilities, skills that ensure effective research activity; readiness for self-development based on awareness of the importance of research in the linguistic and literary field of knowledge; successful experience of scientific research; the ability to solve scientific and methodological problems and implement the integration of education and science in the study of language and literature).
Keywords: pedagogical education, Ukrainian language and literature teacher, research competence of the Ukrainian language and literature teacher